Molecular dynamics simulations of phenolic resin: Construction of atomistic models. (7th April 2015) - Monk, Joshua D.; Haskins, Justin B.; Bauschlicher, Charles W.; Lawson, John W.
Abstract: Algorithms to generate atomistic models of cross-linked phenolic resins suitable for molecular dynamics simulations were investigated. The influence of five parameters (initial volume of uncross-linked material, cross-linking approach, relaxation time, equilibration temperature) on generating cross-linked structures was studied quantitatively using a full factorial sensitivity analysis. The parameters were found to be dependent on the degree of cross linking (D). For low cross-linking, only the equilibration temperature has a significant impact on the final energetics and densities. However, for higher cross-linking (D > 70%), the equilibration temperature, initial volume and cross-linking approach were shown to influence the phenolic structures. Iterative, rather than single step, methods were shown to produce better structures. The initial volume of the uncross-linked material was identified as having the most influence on the final volume of fully cross-linked systems. By optimizing all five parameters, highly cross-linked samples with low energetics and consistent densities could be generated. To validate the models, thermo-mechanical properties of cross-linked phenolic samples were characterized as a function of density and degree of cross-linking. Good agreement with experimental values was obtained for properties such as the glass transition temperature, coefficient of thermal expansion (CTE), elastic moduli, and thermal conductivity. Graphical abstract: Highlights: Analysis of algorithms to produce cross-linked phenolic structures. Iterative cross-linking approach produced low variability high cross-linked configurations. Algorithm parameters influence the final densities and energetics of cross-linked phenolic. Mechanical and thermal properties depend strongly on density and degree of cross-linking. Good agreement with experiments was found for thermal conductivity and Young's modulus.